Lost Archives? Preservation of Ephemeral COVID-19 Data for Research - Balogun, Tolulope (International Journal of Knowledge Content Development & Technology, 2026)
This study explores the significance of web archives in preserving COVID-19-related data and information, emphasizing their potential for future research and their role in documenting major events like the pandemic. Adopting a qualitative research approach, the study utilizes web content analysis to examine the availability of selected COVID-19-related websites on the Internet Archive’s Wayback Machine between January 20, 2020, and April 17, 2020. The analysis focuses on the presence of these webpages and the frequency of their archival crawls. Findings reveal that while the Internet Archive actively harvested COVID-19-related webpages, the frequency of crawls varied, and some pages were not archived as frequently as needed. Rather than examining update rates, the study highlights the accessibility and archival frequency of these webpages. The research is limited in scope, concentrating on a selected group of COVID-19-related websites and emphasizing the importance of web archiving without delving into technical analyses or the issue of online misinformation. Despite these limitations, the study highlights the value of web archives as essential tools for preserving digital records of significant events and demonstrates their potential for future research. By showcasing the function and value of web archiving, this study contributes to ongoing discussions about its role in research, particularly in an interdisciplinary context. It also provides a foundation for discussions on web archiving in Africa, offering insights into its relevance and possibilities for further exploration.